2016
DOI: 10.1002/aic.15418
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and theoretical study of glycerol oxidation to 1,3‐dihydroxyacetone over bimetallic Pt‐Bi catalysts

Abstract: It is important to utilize glycerol, the main by‐product of biodiesel, to manufacture value‐added chemicals such as 1,3‐dihydroxyacetone (DHA). In the present work, the performance of five different catalysts (Pt‐Bi/AC, Pt‐Bi/ZSM‐5, Pt/MCM‐41, Pt‐Bi/MCM‐41, and Pt/Bi‐doped‐MCM‐41) was investigated experimentally, where Pt‐Bi/MCM‐41 was found to exhibit the highest DHA yield. To better understand the experimental results and to obtain insight into the reaction mechanism, density functional theory (DFT) computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 67 publications
0
46
0
1
Order By: Relevance
“…The selectivity of DHA is comparable to that (ca. 80%) observed on the Pt-Bi supported on carbon-based materials with high BET surface areas [19][20][21][22], in which Bi species were observed in the form of Bi2O2CO3 or Bi2O3 and Bi meal, and the geometric blocking effect of active sites by bismuth adatoms was proposed for the high selectivity of DHA. Owing to the difference in Bi species among the Pt-Bi/HT and Pt-Bi/carbon-based materials, herein, the increase in catalytic activity and selectivity for DHA upon introduction of Bi species could be possibly attributed to the strong hydrogen bond between BiOCl on the surface of HT and glycerol molecule, which enormously enhances the adsorption ability of the catalyst towards glycerol.…”
Section: Effect Of Bi Contentmentioning
confidence: 99%
“…The selectivity of DHA is comparable to that (ca. 80%) observed on the Pt-Bi supported on carbon-based materials with high BET surface areas [19][20][21][22], in which Bi species were observed in the form of Bi2O2CO3 or Bi2O3 and Bi meal, and the geometric blocking effect of active sites by bismuth adatoms was proposed for the high selectivity of DHA. Owing to the difference in Bi species among the Pt-Bi/HT and Pt-Bi/carbon-based materials, herein, the increase in catalytic activity and selectivity for DHA upon introduction of Bi species could be possibly attributed to the strong hydrogen bond between BiOCl on the surface of HT and glycerol molecule, which enormously enhances the adsorption ability of the catalyst towards glycerol.…”
Section: Effect Of Bi Contentmentioning
confidence: 99%
“…In Section 2.4, Greeley and coworkers [96] modeled Pt-Bi alloys in glycerol oxidation and revealed the working principles of glycerol dehydrogenation in a synchronized manner at the PtO x and Bi sites. Such information is valuable to understand the intrinsic property related to product selectivity, and would be rather elusive to acquire without the aid of molecular modeling.…”
Section: Modeling Synergistic Bifunctional Catalysts For Glycerol Conmentioning
confidence: 99%
“…Recently, Xiao et al [96] prepared a series of Pt and Pt-Bi catalysts loaded on MCM and ZSM-5 zeolitic supports, such as Pt-Bi/AC, Pt-Bi/ZSM-5, Pt/MCM-41, Pt-Bi/MCM-41, and Pt/Bi-MCM-41. Kinetic measurements showed that bimetallic Pt-Bi loaded on MCM-41 exhibits the highest DHA yield.…”
Section: Catalysts For Glycerol Oxidationmentioning
confidence: 99%
See 2 more Smart Citations